Impact of financial shocks on Islamic banks: Malaysian evidence during 1997 and 2007 financial crises - Kassim, Salina; Abd. Majid, M. Shabri (Emerald Group Publishing, 2010)

(untitled)
Purpose - This study attempts to provide empirical evidences on the impact of financial shocks on the Islamic banks vis-a-vis the conventional banks. Based on the Malaysian experience over two major financial crises, namely the 1997 Asian financial crisis and 2007 US sub-prime crisis, the study aims to test the validity of the proposition that the Islamic banks are more resilient to the financial shocks compared to the conventional banks. Approach - Focusing on the Malaysian data covering three sub-periods, namely, the 1997 Asian financial crisis period (July 1997 - September 1999), the non-crisis period (October 1999 - June 2007) and the 2007 US sub-prime crisis period (July 2007 - September 2009), the study employs the impulse response functions and variance decomposition analysis based on the Vector Auto-Regression (VAR) method. Findings - The results indicate that both the Islamic and conventional banking systems are vulnerable to financial shocks. This is contrary to the popular belief that the Islamic financial system can weather the financial shocks relatively well compared to the conventional financial system due to its interest-free nature. Research implications - The results of this study have important implications for the risk management practices of both the conventional and Islamic banks. Originality/value - This study contributes in providing the empirical evidence on the impact of financial shocks on the Islamic banks. In addition, to our knowledge, there have been no studies comparing of the impacts of the two major crises on the Islamic banking sector.